P158 Evaluation of sexual health service use at baseline (2014) in South East London. (30th June 2016) - Turner, Katy; Looker, Katharine; Syred, Jonathan; Bernard, Sharmani; Baraitser, Paula
Abstract : Background/introduction: Lambeth and Southwark have poor sexual health outcomes compared with the rest of England. We wished to evaluate an intervention to improve access to sexual health services through online STI testing and contraceptive provision. Aim(s)/objectives: This study describes baseline service use in Lambeth and Southwark in 2014 prior to the introduction of online services. We present our methodology for evaluating service use across the boroughs. Methods: We collated baseline demographic and clinical data from all sexual health service providers (genitourinary medicine and community sexual health clinics) in Lambeth/Southwark, South East London, for one calendar year (2014). Individual level clinic data were merged, together with Office for National Statistics (ONS) on index of multiple deprivation for area (LSOA) of residence. We summarise the main type of service used and define each attendance as possible to be provided "online" (basic STI test, repeat oral contraception) or requiring "offline" services (e.g. clinical exam, surgical intervention, symptoms, long-acting contraception). Results: We collected over 127, 000 attendance records for sexual health services in Lambeth and Southwark during 2014. All clinics reported consistent levels of activity during each quarter. Up to 40% of attendances could potentially be provided online based on clinic coding. Discussion/conclusion: The low monthly variation in attendances suggests that current services are operating at capacity. Understanding current service use will enable evaluation of online services to assess whether providing online services 1) increases capacity, 2) reaches new population groups 3) improves access for high risk groups.